1999
DOI: 10.1016/s0014-5793(99)00797-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a functionally active human hepatic UDP‐glucuronosyltransferase (UGT1A6) lacking the N‐terminal signal sequence in the endoplasmic reticulum

Abstract: UDP-glucuronosyltransferase 1A6 (UGT1A6) is a membrane glycoprotein of the endoplasmic reticulum playing a key role in drug metabolism. It is synthesized as a precursor with an N-terminal cleavable signal peptide. We demonstrate that deletion of the signal peptide sequence does not prevent membrane targeting and integration of this human isoform when expressed in an in vitro transcription-translation system, as shown by N-glycosylation, resistance to alkaline treatment and protease protection. Furthermore, UGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…If the truncated DcUGT2 protein is indeed targeted to the ER without the putative signal peptide, another unknown ER-targeting signal must be present in the DcUGT2 protein and clearly not contained within the transmembrane domain/cytoplasmic tail. Such a signal has, in fact, been demonstrated to occur within an amino acid stretch, encompassing residues 140–240 of the human UGT1A6, although an exact motif was not defined 33 , 34 . Expression of UGT1A6 without the sequence encoding the N-terminal signal peptide showed that the ΔSP-UGT1A6 protein was translocated into and retained in the ER via this 100 amino acid stretch in mammalian cells 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the truncated DcUGT2 protein is indeed targeted to the ER without the putative signal peptide, another unknown ER-targeting signal must be present in the DcUGT2 protein and clearly not contained within the transmembrane domain/cytoplasmic tail. Such a signal has, in fact, been demonstrated to occur within an amino acid stretch, encompassing residues 140–240 of the human UGT1A6, although an exact motif was not defined 33 , 34 . Expression of UGT1A6 without the sequence encoding the N-terminal signal peptide showed that the ΔSP-UGT1A6 protein was translocated into and retained in the ER via this 100 amino acid stretch in mammalian cells 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Such a signal has, in fact, been demonstrated to occur within an amino acid stretch, encompassing residues 140–240 of the human UGT1A6, although an exact motif was not defined 33 , 34 . Expression of UGT1A6 without the sequence encoding the N-terminal signal peptide showed that the ΔSP-UGT1A6 protein was translocated into and retained in the ER via this 100 amino acid stretch in mammalian cells 33 , 34 . The amino acid alignment of DcUGT2 to UGT1A6 indeed identified regions of homology between the two proteins in this 100 amino acid stretch, but whether the ER-targeting signal is contained within these regions remains to be established (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UGTs are synthesized as precursors of ~530 residues containing an N-terminal signal peptide that mediates the integration of the polypeptide chain into the ER (Mackenzie and Owens, 1984; Ouzzine et al, 1999a, 1999b). The signal peptide is subsequently cleaved and the protein is N-glycosylated.…”
Section: Introductionmentioning
confidence: 99%
“…Following membrane integration, the N-terminal signal peptide is cleaved and the enzyme is N -glycosylated in the ER lumen. Notably, other internal topological elements within the UGTs might be required to regulate the integration process, as demonstrated for UGT1A6 [ 49 , 50 ]. In this way, the UGTs become mature ER enzymes of just over 500 residues [ 1 ].…”
Section: Compartmentation Hypothesismentioning
confidence: 99%